Modern methods of foreign language teaching in universities (Eurasian Journal of Philology Science and Education, 2016)
This article describes the formation of linguistic competence of students during the English lessons with modern innovative technologies, in particular using problematic teaching method. The key concept of problem-based learning is a «problem situation», which is created by a teacher with educational purpose. It involves a complex theoretical or practical task that requires study, extension, research, coupled with certain conditions and circumstances that create a particular situation. This method of teaching also improves the process of learning a foreign language and contributes to achieving better results, developing the intellectual potential of students, and also it opens up opportunities for creative cooperation of the teacher and the student. The paper presents the basic forms of problem-based learning, its specificity and levels. It also provides illustrative examples of different types of classes with the use of innovative learning technologies. We conclude that the problematic technique is one of the most productive and relevant methods of learning a foreign language at the moment.
Keywords: linguistic competence; foreign language; innovative tech¬nologies; problem method of training.